O sistema informal de sementes crioulas e as guardiãs de sementes da vida: o protagonismo de mulheres na região central do RS - Bernardo, Marina Augusta Tauil (2021)
This dissertation presents reflections on the construction of the legal system related to Creole seeds, based on the precept that the “discovery” of Brazil was, and continues to be, a great commercial enterprise that permeates in two ways: the private appropriation of its natural resources and the struggles that resist this process. The agro-export production model spread from capitalist expansion and industrial development linked to the use of transgenic seeds, continues to spread with the connivance of large landowners and the Brazilian state. On the other hand, through the contributions of family farmers, the informal seed system resists, even if the margin of the capitalist model of agro-industrial agricultural production destined for the export of commodities is maintained. The struggle of rural women is accentuated by the fact that their actions are made invisible, due to the withdrawal of protagonism in their different areas of activity. With this, the main objective of the work, through the use of the qualitative research procedure, bibliographic and documentary survey, with the use of semi-structured interview technique and the use of the “Rio da Vida” tool, is to enable four guardians of Creole seeds considered as references in the central region of Rio Grande do Sul report their trajectories and perceptions regarding their productive and reproductive spheres. In a conclusive way, peasant women through their daily practices exercise in a local way the conservation of genetic heritage and traditional knowledge associated with the management of Creole seeds and it is necessary, therefore, to redefine the role of these women who historically suffer oppression and that are exploited doubly: by capital and patriarchy.